GENEALOGY OF TABUT RITUAL CULTURAL AESTHETICS OF THE SUMATRAN WEST COASTAL COMMUNITY - KHANIZAR, KHANIZAR; Wirawan, AA Bagus; Sulistyawati, Sulistyawati; Sukardja, Putu (E-Journal of Cultural Studies, 2016)
The tabut ritual is performed in the West Coastal area of Sumatera to commemorate Imam Husein Bin Ali Abi Thalib when he was captured by the soldiers of Yazid Muawiyah in Padang Karbala. It is performed once a year, from the first to the tenth of Muharam, which is counted based on the Hijirah year. This present study is intended to investigate the form, function, and meaning of the genealogy of the tabut ritual which is performed in and as the identity of the West Coastal Area of Sumatera. It tries to (1) discuss and deconstruct the values of such a ritual as the community’s identity which tightens the cultural value of the Sumatran West Coastal community; (2) exploits the tabut ritual as the form of the Sumatran West Coastal community’s identity; (3) apply the function of the ethnical aesthetics; (4) explain the aesthetic meaning in its relation to religion and customs and traditions. Three theories were used to answer the problems of the study; they are the theory of genealogy proposed by Michel Foucault and the postcolonial theory. What could be concluded from the present study are as follows. The genealogical forms of the tabut ritual which is performed in the  West Coastal are of Sumatera reflects the community’s cultural aesthetics and functions to purify the soul; it also reflects religiosity, mystical and aesthetic experience  and the hegemony which exceeds the postcolonial patronage, meaning that such a ritual has the purification function. It also reflects the cosmological aesthetics of the supporting community. It has deconstruction and aesthetical genealogical meaning.